Implementasi Program Keagamaan Sebagai Upaya Pembiasaan Nilai-Nilai Keislaman Siswa di SMP IRA Medan - Muzdalifah Rohami Harahap; Juli Julaiha Pulungan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to describe the implementation of religious programs as an effort to instill Islamic values in students at SMP IRA Medan. This study employs a qualitative, descriptive approach. Data collection techniques included interviews, observations, and documentation. The research subjects comprised the school principal, Islamic Religious Education teachers, and students. The results indicate that the religious program at SMP IRA Medan is implemented in a structured manner and integrated into routine school activities, such as Dhuha prayer, congregational Zuhr prayer, self-reflection (muhasabah), and evening worship sessions. The program involves all students under direct teacher supervision, thereby fostering the internalization of Islamic values such as discipline, responsibility, honesty, and mutual respect. Nevertheless, several challenges were identified in the implementation, including limited facilities and infrastructure, low consistency among some students, the influence of the family environment, and time constraints for conducting the activities. To address these challenges, the school has taken various measures, such as providing guidance and motivation to students, increasing supervision, employing a persuasive approach, and conducting regular program evaluations. The findings of this study indicate that the consistent implementation of religious programs, supported by a conducive school environment, can serve as an effective means of fostering students’ religious character through a continuous process of habit formation.